The educational manager in the public school: challenges and perspectives (Revista Brasileira Multidisciplinar, 2020)
Considering the challenges faced by the manager within a public institution of education, the objective of this research is to understand the role of this professional within this administrative sphere and to identify the difficulties in the democratic and non-autonomous management of financial resources that are made available to you. The research also discusses the importance of democratic management in the public school environment, in its multiple aspects. To do so, the methodology used was focused on the bibliographic research in which the authors supported and complemented the discussions presented, bringing contributions to this extensive field of research. The reflections obtained contribute to the improvement of the public school facing the challenges of contemporary society.